Современный болгарский и русский политический дискурс ‒ тенденции, сходства, закономерности - Simeonova, Kristiyana (Acta Universitatis Lodziensis. Folia linguistica rossica, 2019)
The paper is devoted to some interesting language phenomena occurring today in the Bulgarian and Russian socio-political vocabulary. These phenomena are of a similar nature, which can be attributed to the similar nature of some political and economic processes in the two countries. Such phenomena typical of both languages are manifested in a growing influence exerted on the socio-political vocabulary by extra-linguistic factors, emergence of an increasingly expressive language, eradication of part of the vocabulary related to the period of socialism from active use, and others. The author points to many interesting examples, taken mostly from the Russian mass-media, to illustrate these phenomena. The main conclusion of the study is that today’s trends and phenomena in the Bulgarian and Russian socio-political discourse are of a similar nature. Certainly, this should not come as a surprise given the genetical relationships between the two languages.